Real-Time Estimation of Aerobic Threshold and Exercise Intensity Distribution Using Fractal Correlation Properties of Heart Rate Variability: A Single-Case Field Application in a Former Olympic Triathlete - Gronwald, Thomas; Berk, Sander; Altini, Marco; Mourot, Laurent; Hoos, Olaf; Rogers, Bruce (Frontiers in Sports and Active Living, 2021)
A non-linear heart rate variability (HRV) index based on fractal correlation properties called alpha1 of Detrended Fluctuation Analysis (DFA-alpha1), has been shown to change with endurance exercise intensity, crossing a value of 0.75 at the aerobic threshold (AT) in a population of recreational runners. Its unique advantage is that it provides information about current absolute exercise intensity without prior calibration to conventional lactate or gas exchange testing. A real-time estimation of this metric has several significant advantages. These include near instantaneous assessment of the AT during an exercise ramp or constant power intervals as well as information about time spent above the AT. Until of late no mobile based product could display DFA-alpha1 in real-time using off the shelf consumer products. However, an app designed for iOS devices, HRV Logger, was recently revised to display DFA-alpha1 from commonly used heart rate monitors. This brief research report illustrates the potential merits of immediate knowledge of this metric for the purposes of aerobic threshold determination as well as exercise intensity distribution at the zone 1 to 2 transition in a former Olympic triathlete. Three scenarios are presented, 1) calculation of a HRV threshold (HRVT) as a proxy for AT using Kubios HRV software via a typical cycling ramp, 2) determination of the HRVT during real-time monitoring using a cycling stage test, 3) a simulated training ride with enforcement of low intensity boundaries and real-time HRVT confirmation. To assist those interested in implementation, recommendations for the practical application will be given.